2017
DOI: 10.1590/0103-6440201701523
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Mandibular Cortical in Patients With Type 1 Diabetes Mellitus Combined with Poor Glycemic Control

Abstract: In this study we analyzed the mandibular cortical bone of patients with type 1 diabetes mellitus (T1DM) and non-diabetic. Fifty patients with T1DM and 100 non-diabetic ones paired by age and gender were analyzed. Two double-blinded observers evaluated 150 digital panoramic images of both groups. The mandibular cortical bone was analyzed using the Mandibular Cortical Index (MCI), Mental Index (MI), Gonial Index (GI), Antegonial Index (AI) and Upper and Lower Panoramic Mandibular Indexes (UPMI and LPMI), with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Failure to control T1DM and delayed diagnosis can have a harmful effect on bone development and mineralization (11). In the study, a decrease in mandibular cortical bone was observed in children with T1DM compared to non-diabetic children, and this was associated with poor control of T1DM (8). Similarly, in our study, MI, MCW, and AI values were observed to be lower in the children with T1DM than in the healthy.…”
Section: Gonial Index (Gi)supporting
confidence: 68%
See 1 more Smart Citation
“…Failure to control T1DM and delayed diagnosis can have a harmful effect on bone development and mineralization (11). In the study, a decrease in mandibular cortical bone was observed in children with T1DM compared to non-diabetic children, and this was associated with poor control of T1DM (8). Similarly, in our study, MI, MCW, and AI values were observed to be lower in the children with T1DM than in the healthy.…”
Section: Gonial Index (Gi)supporting
confidence: 68%
“…All examinations and practices were approved by the local ethics committee and were conducted in accordance with the Helsinki Declaration of 1964 and its subsequent versions (No: 441/2022). According to Limeira et al (8), G*Power analysis determined that at least 35 children should be included in each group, with a 95% confidence interval and 80% power.…”
Section: Study Groupmentioning
confidence: 99%
“…analyzed MCI among individuals with type 1 Diabetes Mellitus. The authors declared mandibular cortical alterations in all age groups and in the both genders [35]. Moreover, we failed to prove an influence of vitamin D and calcium use on MCI category: subjects who used vitamin D and calcium belonged to all three morphological MCI groups and sample sizes were small.…”
Section: Discussionmentioning
confidence: 74%
“…While Fuusager et al 24 found a negative correlation between poor glycemic control and the BMD Z-score, like other studies 25,26 , some studies have not found such a correlation. 27,28 Limeira et al 3 found lower values in the mental, gonial, and antigonial indices and the upper and lower PMI parameters in patients with poorly controlled type 1 DM than in non-diabetic patients. Nemtoi et al 29 evaluated the bone quantity and quality of the mandible of DM patients with cone beam-computed tomography.…”
Section: Discussionmentioning
confidence: 96%
“…2 Bone mineral density (BMD) represents the quantity of bone tissue in a specific volume of bone. 3 Dental radiographs, especially panoramic images, can show a loss of BMD. 4,5 For this purpose, different panoramic radiomorphometric indices, such as mandibular cortical width (MCW), panoramic mandibular index (PMI), mandibular cortical index (MCI), and simple visual estimation (SVE), have been used in literature.…”
Section: Introductionmentioning
confidence: 99%